2008
DOI: 10.1002/cbic.200800341
|View full text |Cite
|
Sign up to set email alerts
|

S‐Adenosyl‐L‐Methionine Hydrolase (Adenosine‐Forming), a Conserved Bacterial and Archeal Protein Related to SAM‐Dependent Halogenases

Abstract: Keywords DUF62; halogenation; hydrolase; S-adenosyl-L-methionine; SalinisporaS-Adenosyl-L-methionine (SAM) is a ubiquitous molecule that participates in various biochemical reactions, second only to ATP as the most frequently used enzyme substrate. [1] The recently described SAM-dependent halogenases involved in the biosynthesis of secondary metabolites in actinomycetes represent a new family of SAM-binding proteins [2,3] that catalyze the nucleophilic displacement of L-methionine (L-met) from SAM with halides… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
0
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 30 publications
(39 citation statements)
references
References 32 publications
(42 reference statements)
2
35
0
2
Order By: Relevance
“…We recently showed that a DUF62 ortholog from Salinispora arenicola (86% identity to Strop_1405) has SAM hydrolase but no halogenase activity in vitro (33), which was independently reported with an archaeal DUF62 (34). Together with in silico analysis, these data suggest divergent evolution of SAM-dependent halogenases from SAM hydrolases (33) and clarify the salL mutant phenotype.…”
Section: Discussionsupporting
confidence: 52%
“…We recently showed that a DUF62 ortholog from Salinispora arenicola (86% identity to Strop_1405) has SAM hydrolase but no halogenase activity in vitro (33), which was independently reported with an archaeal DUF62 (34). Together with in silico analysis, these data suggest divergent evolution of SAM-dependent halogenases from SAM hydrolases (33) and clarify the salL mutant phenotype.…”
Section: Discussionsupporting
confidence: 52%
“…Protein sequence alignments show that Gly131 (SalL numbering) is conserved in most cases, while Tyr70 is replaced by nonpolar, aliphatic residues including Val, Gly and Ile. 306308 On the basis of structure–function studies of FlA and SalL, these DUF62 proteins would most likely not act as nucleophilic halogenases due to the predicted larger size of the halide binding pocket and likely presence of water in the active site. In fact, two DUF62 proteins have been biochemically analyzed, i.e.…”
Section: S-adenosyl-l-methionine-dependent Halogenasesmentioning
confidence: 99%
“…Only iodide was accepted by SARE1364 but with K m for iodide (20 mM, which is 40,000-fold higher than the concentration of iodide in seawater) and k cat (0.5 h −1 ) that do not appear biologically relevant. 306 Moreover, DUF62 proteins contain a strictly conserved Asp-Arg-His triad that is absent in fluorinase and chlorinase and is proposed to be involved in water activation for SAM hydrolysis (Figure 31). 306308 It remains to be shown if this SAM hydrolase activity measured in vitro is physiologically relevant.…”
Section: S-adenosyl-l-methionine-dependent Halogenasesmentioning
confidence: 99%
“…Der Einbau von Fluorid ist allerdings wegen subtiler Umlagerungen in der Halogenbindungstasche, wie sie bei hochaufgelösten Kristallstrukturen von SalL und Mutanten des aktiven Zentrums beobachtet wurden, mit SalL nicht möglich. Zusammen mit der Fluorinase FlA [68] und den kürzlich entdeckten SAM-Hydroxid-Adenosyltransferasen (duf-62) [70][71][72] bildet SalL eine neue Klasse SAM metabolisierender Enzyme. [73] Die Bildung von 5'-Chlor-5'-desoxyadenosin (49, 5-ClDA) initiiert eine komplexe Biosyntheseroute zu 47, wobei alle dafür entscheidenden Gene im salCluster zu finden sind (Schema 5 a, blau eingefärbt), wie durch Gen-Inaktivierung und chemische Komplementierung aufgezeigt wurde.…”
Section: Entdeckung Der Salinosporamidfamilieunclassified